Characteristics of Agricultural Land in the Floodplain Area of the Tarusan Watershed, Pesisir Selatan, West Sumatra - Sandi, Nofrita; Gusmini; Yasin, Syafrimen; Herviyanti; Prasetio, Teguh Budi; Rasyidin, Azwar; Nasution, Nur Fadillah (TERRA : Journal of Land Restoration, 2025)
The numerous rivers and high rainfall in West Sumatra often lead to flooding, which affects several land uses such as settlements, plantations, and agriculture. During floods, water transports various materials from upstream to downstream, such as sand, mud, and clay, which are deposited in certain riverbanks. This study aimed to examine the soil fertility characteristics in the floodplain area. The method used in this research was a survey method with purposive random sampling at two soil depths: 0 – 30 cm and 30 – 60 cm. Samples were taken from two land uses: dryland agriculture and wetland agriculture. The parameters analyzed were texture, organic carbon, bulk density, total pore space, pH in H2O, available P, total N, and exchangeable potassium. The results of the study for each parameter showed that the soil texture in dryland agriculture was sandy loam, while in wetland agriculture, it was clay loam. Organic carbon was classified as low (1.31%–1.62%). Wetland soils had higher porosity (57.67%–61.40%) and lower bulk density (1.01–1.10 g/cm³) compared to dryland soils. Soil pH was acidic (4.52–4.95). Available P, total N, and exchangeable potassium were higher in wetland soils than in dryland soils. In conclusion, the results of the study indicate that the soil properties, both physical and chemical, in wetland agriculture were better than in dryland agriculture, although no significant differences were found.